Teaching bedside ultrasound to medical students. (8th August 2017) - Ang, John; Doyle, Brian; Allen, Penny; Cheek, Colleen
Summary: Objective: Point‐of‐care ultrasound (POCUS) assists in the rapid diagnosis of conditions in the Emergency Department (ED). POCUS has been introduced to international medical curricula; however, there is no described implementation of clinically focused POCUS education in Australian medical schools. We wanted to investigate whether a formal curriculum can be effective and feasible in an Australian medical school. Methods: Pre–post intervention study of a focused curriculum based on the Extended Focused Assessment with Sonography in Trauma (E‐FAST) examination, consisting of online and practical teaching, was implemented for Year‐4 and ‐5 medical students. An online questionnaire was used to measure knowledge, image interpretation and confidence prior to the intervention. After the intervention and ED placement, the questionnaire was repeated and students were assessed performing the E‐FAST examination on a healthy volunteer. Results: Twenty‐seven students participated in both the pre‐intervention and post‐intervention questionnaires. There was a significant improvement in confidence in performing the E‐FAST after the intervention [p < 0.001]. There was also a significant improvement in ultrasound knowledge and image interpretation skills. For the formative assessment, the mean score was 31.8 out of 33 and 22 of 27 students (82%) passed the assessment. There is no described implementation of clinically focused point‐of‐care ultrasound education in Australian medical schools Conclusions: We have demonstrated that a focused curriculum can improve POCUS knowledge and skills. The curriculum was feasible and well received. With global trends to include POCUS in medical education, Australian institutions should consider upskilling their medical graduates.